Pakistan’s Global Trade Potential with Selected Trading Partners: A Gravity Model Approach Using Static and Dynamic Panel Data - Siddique, Muhammad; Quddus, Muhammad Abdul; Iqbal, Asim (iRASD Journal of Economics, 2022)
This research study employs a gravity model to explore Pakistan's trade potential from 2000 to 2020. China, United Arab Emirates (UAE), Saudi Arabia (KSA), Kuwait, United States (USA), Malaysia, Japan, India, Singapore, Afghanistan, Iran, Spain, Germany, United Kingdom (UK) and Belgium are among our significant trading partners. The study uses both static and dynamic econometric techniques to capture the trade potential of Pakistan. The findings from both methodologies are comparable, indicating that economic size and distance have a significant effect on bilateral trade. Furthermore, throughout the research period, political globalization is determined to be considerable and has an important influence on the economic masses. These factors support the theoretical model(s) that Pakistan and Pakistan’s trading partners with economic integration, political globalization, and distance all depict a significant impact on trade relations.